Hyperglycemia and nocturnal systolic blood pressure are associated with left ventricular hypertrophy and diastolic dysfunction in hypertensive diabetic patients - Felício, João S.; Pacheco, Juliana T.; Ferreira, Sandra R. [UNESP]; Plavnik, Frida; Moisés, Valdir A.; Kohlmann Jr., Oswaldo; Ribeiro, Artur B.; Zenella, Maria T. (Springer Nature, 2006)
Background: The aim of this study was to determine if hypertensive type 2 diabetic patients, when compared to patients with essential hypertension have an increased left ventricular mass index (LVMI) and a worse diastolic function, and if this fact would be related to 24-h pressoric levels changes. Methods: Ninety-one hypertensive patients with type 2 diabetes mellitus (DM) (group-1 [G1]), 59 essential hypertensive patients (group-2 [G2]) and 26 healthy controls (group-3 [G3]) were submitted to 24-h Ambulatory Blood Pressure Monitoring (ABPM) and echocardiography (ECHO) with Doppler. We calculated an average of fasting blood glucose (AFBG) values of G1 from the previous 4.2 years and a glycemic control index (GCI) (percentual of FBG above 200 mg/dl). Results: G1 and G2 did not differ on average of diurnal systolic and diastolic BP. However, G1 presented worse diastolic function and a higher average of nocturnal systolic BP (NSBP) and LVMI (NSBP = 132 ± 18 vs 124 ± 14 mmHg; P < 0.05 and LVMI = 103 ± 27 vs 89 ± 17 g/m2; P < 0.05, respectively). In G1, LVMI correlated with NSBP (r = 0.37; P < 0.001) and GCI (r = 0.29; P < 0.05) while NSBP correlated with GCI (r = 0.27; P < 0.05) and AFBG (r = 0.30; P < 0.01). When G1 was divided in tertiles according to NSBP, the subgroup with NSBP≥140 mmHg showed a higher risk of LVH. Diabetics with NSBP≥140 mmHg and AFBG>165 mg/dl showed an additional risk of LVH (P < 0.05; odds ratio = 11). In multivariate regression, both GCI and NSBP were independent predictors of LVMI in G1. Conclusion: This study suggests that hyperglycemia and higher NSBP levels should be responsible for an increased prevalence of LVH in hypertensive patients with Type 2 DM. © 2006 Felicio et al; licensee BioMed Central Ltd.